NATIONAL ARBITRATION AND FOREIGN ARBITRATION AND THE EFFECTS OF EXCLUDING IRAQIARBITRATION IN THE DRAFT IRAQI ARBITRATION LAW - Rouaa Ali Attiya; Prof. Dr. Achraf Rammal (American Journals Publishing, 2024)
The arbitration law, whether national or foreign, is one of the important topics and arbitration includes two types, national arbitration and foreign arbitration, and it is considered a means of settling disputes and disputes between different parties outside the judiciary Due to the importance of the national economy and the increase in the proportion of investments, the arbitration law in the country is of great importance in terms of attracting investment, as they are more reluctant in a country that does not provide legal protection and strong legal cover for local arbitration The draft Iraqi arbitration law must take into account successful international practices and seek to find a balance between local and international standards to ensure a reliable and effective arbitration environment that contributes to enhancing confidence between the disputing parties and in the Iraqi legal system.The Iraqi legal system has defined commercial arbitration since 1928 with Law No. (34) of 1928, which includes the ratification of the Protocol on Arbitration Terms signed in Geneva on 9/24/1923 and called (Protocol on Arbitration Clauses Geneva). The aforementioned protocol included the validity of the agreements between the contracting states that included Resolving disputes related to commercial and other issues through arbitration.
Keywords: National, foreign, arbitration, draft Iraqi arbitration law